A Bayesian Structural Equation Model to Predict Quality of Life in European Older Adults - José M. Tomás; Aitana Sanz; Zaira Torres (European Journal of Investigation in Health, Psychology and Education)
The ultimate goal of developed societies is to age with quality of life, but this concept is broad, and few studies have addressed which variables specifically affect its dimensions. This study aims to test a model for predicting the impact of frailty, pain, and loneliness on the four dimensions of quality of life (control, autonomy, pleasure, and self-realization). Data were drawn from a sample of 61,355 Europeans from the Wave 7 of the SHARE project, aged 60 or older (M = 71.87, SD = 8.22), from which 55.9% were females. Statistical analyses included a fully Bayesian structural equation model that evidences the significant effect of loneliness, frailty, and pain on the four dimensions of quality of life. The variables have an unequal impact on the different dimensions’ loneliness was the main predictor for the dimensions control, autonomy, and pleasure, while frailty was the main predictor to self-realization. This study supports the need to address these variables to intervene on the different aspects of quality of life in old age.